1984
DOI: 10.1121/1.390568
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds of perception of vibration in recumbent men

Abstract: The thresholds of perception of vibration by recumbent men are a significant index for the governmental agency concerned with regulation of vibration exposure. The thresholds of perception of continuous sinusoidal vibrations and single and multiple bursts of sinusoidal vibrations in the horizontal and vertical directions were investigated in recumbent men. We found that the threshold curves, as a function of the frequency, had different characteristics for vertical vibrations than for horizontal vibrations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…With the fully reclined backrest (90), the frequency-dependence of the equivalent comfort contours obtained in the present study are broadly similar to thresholds and equivalent sensation contours reported in previous studies (e.g., Miwa and Yonekawa, 1969;Szameitat and Dupuis, 1976;Miwa et al, 1984;Yonekawa et al, 1999;Gibson, 1978: Figure 9). The contours reported by Gibson (1978) indicate less discomfort at high frequencies, but subjects lay on a stretcher with undefined dynamic properties that may have reduced the transmission of high-frequency vibration to the body.…”
Section: Effect Of Backrest Inclinationsupporting
confidence: 90%
“…With the fully reclined backrest (90), the frequency-dependence of the equivalent comfort contours obtained in the present study are broadly similar to thresholds and equivalent sensation contours reported in previous studies (e.g., Miwa and Yonekawa, 1969;Szameitat and Dupuis, 1976;Miwa et al, 1984;Yonekawa et al, 1999;Gibson, 1978: Figure 9). The contours reported by Gibson (1978) indicate less discomfort at high frequencies, but subjects lay on a stretcher with undefined dynamic properties that may have reduced the transmission of high-frequency vibration to the body.…”
Section: Effect Of Backrest Inclinationsupporting
confidence: 90%
“…x-axis) whole-body vibration of supine recumbent subjects (e.g. [22,23,24]) (Figure 11). At frequencies greater than 5 Hz, the frequencydependence of the thresholds in the present study is broadly consistent with the frequencydependence of thresholds for supine subjects, although the thresholds are about 6 dB higher than those reported by Miwa et al [23] and Yonekawa et al [24] and about 3 dB higher than those reported by Parsons and Griffin [22].…”
Section: Figure 10 About Herementioning
confidence: 99%
“…The different psychophysical methods used in these studies may also have contributed to the differences in thresholds. Miwa et al [23] used the method of limits with 10-s stimuli whereas both Yonekawa et al [24] and Parsons and Griffin [22] used the method of adjustment. At low frequencies, the increased sensitivity to backrest vibration evident in the thresholds of the present study is likely to have arisen from relative motion between the vibrating back and the stationary seat or stationary headrest.…”
Section: Figure 10 About Herementioning
confidence: 99%
“…The thresholds obtained with the fully reclined backrest (90) have a similar frequencydependence to the averaged sensitivity to longitudinal horizontal vibration of recumbent subjects ( Figure 8; Yonekawa, 1969, Szameitat andDupuis, 1976;Miwa et al, 1984;Yonekawa et al, 1999). Miwa and Yonekawa determined the relative sensitivity of different parts of the recumbent body exposed to longitudinal vibration (i.e., head, back, buttocks plus femora, calves plus heels, and the whole body).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%